Improving Engine Cooling Performance through Slotted Fin Design: A Steady-State Thermal Analysis Study - N. Muthuram; Brajesh Kumar Kanchan; K. U. Ajith Kumar (Journal of Heat and Mass Transfer Research)
The engine fin is an essential component that significantly impacts the cooling system's effectiveness and overall performance. Although the engine fin is used to dissipate heat generated, an attempt to enhance the effective surface area for the fin needs to be addressed. This research aims to enhance the effectiveness of engine cooling systems through the fin design, which may involve incorporating slots to expand the surface area and improve overall efficiency. The analysis involved two fin geometries, rectangular and cylindrical fins, made of Aluminum 1100 material. The design models are created using the computer-aided design software PTC CREO Parametric 6.0., and steady-state thermal analysis and modal analysis were performed using ANSYS 2023 R1. The steady-state thermal analysis results indicate that the slotted cylindrical fin design demonstrated the highest heat transfer rate compared to the conventional fin design. The results from this study are expected to provide valuable performance in improving heat dissipation.